1990
DOI: 10.1016/s0886-3350(13)80779-1
|View full text |Cite
|
Sign up to set email alerts
|

New refractive method for laser thermal keratoplasty with the Co:MgF2 laser

Abstract: We have observed corneal curvature changes from laser thermal keratoplasty with a Co:MgF2 laser. We studied corneal curvature changes in rabbits and have identified specific treatment patterns and laser parameters that can correct myopia and astigmatism. These corneal changes, some as large as 8 diopters, have been stable for at least one year, and slitlamp examination demonstrates clear central corneas with normal appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…17(a)). Seiler and others [36]- [38] recently demonstrated that the refractive power of the cornea can be adjusted by shrinkage of corneal collagen fibers with lasers emitting around 2 pm [39]. A small series of hyperopic patients treated with the holmium laser coupled to a fiber-optic probe delivery system has shown reasonable predictability and fair stability of the refractive outcome.…”
Section: B Laser Photothermal Keratoplasty (Lptk) or Photoshrinkingmentioning
confidence: 99%
“…17(a)). Seiler and others [36]- [38] recently demonstrated that the refractive power of the cornea can be adjusted by shrinkage of corneal collagen fibers with lasers emitting around 2 pm [39]. A small series of hyperopic patients treated with the holmium laser coupled to a fiber-optic probe delivery system has shown reasonable predictability and fair stability of the refractive outcome.…”
Section: B Laser Photothermal Keratoplasty (Lptk) or Photoshrinkingmentioning
confidence: 99%
“…Later, other authors [4,5,6,9,15] described treatments for keratoconus. Fyodorov and Caster [3] were the first to apply an invasive method: a retractable steel needle, heated to 600C, was inserted deep into the corneal stroma.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal laser source for LTK should provide a uniform and continuous heating 10 within the irradiated volume down to the '-posterior stroma in order to apply a constant optimal temperature for cornea! shrinkage -- temperature8.…”
mentioning
confidence: 99%